The role of the public accounts committee in enhancing government accountability in Malaysia - Saleh, Z.; Abu Hasan, H. (2015)
This chapter provides an overview of the institutional framework of Malaysia's federal Public Accounts Committee (PAC), and the Committee's role in enhancing public sector accountability. The development of the PAC and its relationship to the government structure in Malaysia are discussed alongside other institutions within the administrative framework of accountability. These include the Accountant General's Department and the National Audit Department. A description of the PAC's powers, responsibilities, membership and working practices precedes a discussion on its effectiveness in supporting the enhancement of accountability. In addition, this chapter also cites cases examined by the PAC that were highlighted in the media.